Penggunaan Hadis Daif Dalam Fatwa Mengenai Wasiat Di Malaysia Serta Langkah Penyelesaiannya - Muhamad Asni, F. A. H.; Sulong, J.; Ismail, A. (Universiti Sains Islam Malaysia, 2024)
Hadith derived from wahyu and it is very authoritative arguments in Syarak besides the Quran. It is the most important resource in the fatwa production process. Generally, the Prophet Muhammad appeared more than 1,400 years ago and its authenticity is carefully guarded by the scholars among them with organising sanad knowledge to prevent from dhaif and false hadiths. Hence, guarantee the authenticity of the Hadith in argue is the responsibility of the mufti so that the fatwa issued precise and strong. Otherwise, if arguing with da'if hadith implies poor fatwa results from the point of the argument. Therefore, this study aims to identify the da'if hadiths which are used as an arguments or istidlal in the fatwa results on the will in the Mufti States. This research was conducted qualitatively by reference to the debate on the books of fiqh and hadith, the provisions of the law, fatwa, decisions and related papers. The results showed that there are daif hadith used in the wajibah will fatwa and will to the heirs and researchers have provided an alternative view. Thus, the study suggested that fatwas are reviewed in terms of his submission, particularly involving the hadith arguments.